DIFFERENCES IN TOOTHBRUSHING KNOWLEDGE WITH COUNSELING USING DEMONSTRATION AND SIMULATION METHODS STUDENTS AT SDN 06 TALUAK IV SUKU, BANUHAMPU DISTRICT, AGAM REGENCY (Proceedings OPTIMAL, 2026)
Dental and oral health issues remain a significant public health concern in Indonesia, particularly in regional areas such as Agam Regency. A primary risk factor contributing to the high prevalence of dental diseases among school-aged children is a profound lack of knowledge regarding proper toothbrushing techniques and oral hygiene maintenance. This study aimed to evaluate and compare the effectiveness of two different educational interventions—the demonstration method and the simulation method—in improving toothbrushing knowledge among fourth, fifth, and sixth-grade students at SDN 06 Taluak IV Suku, Banuhampu District, Agam Regency.Utilizing a quasi-experimental design with a pretest-posttest approach, a total of 60 students were selected through a total sampling technique. The respondents were divided into two intervention groups: one receiving counseling via the demonstration method and the other through the simulation method. Data were meticulously collected using structured knowledge questionnaires and direct observations, which were subsequently analyzed using the non-parametric Mann-Whitney U statistical test. The results demonstrated a notable increase in knowledge scores across both groups; however, the simulation group exhibited a more substantial improvement, rising from a baseline of 69% to 84%, compared to the demonstration group which increased from 70% to 82%. Statistical analysis confirmed a significant difference between the two interventions ($p = 0.000$), indicating that the simulation method, which emphasizes active participation and hands-on practice, is more effective than passive demonstration. These findings suggest that incorporating interactive simulation into school dental health programs (UKGS) is essential for fostering better oral health literacy and long-term behavioral changes in children.